Pengaruh Produk Domestik Bruto, Kurs Dollar Amerika Serikat, Inflasi dan Konsumsi Terhadap Impor Makanan dan Minuman Olahan di Indonesia - Darma, Anak Agung Angga; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 6, Juni 2019, pp (1181-1442), 2019)
Food and beverages are the one of the primary commodities needed by every human being in the world. Processed foreign food and beverage products are in great demand by the people of Indonesia because of changes in consumption patterns. This study aims to determine the effect of gross domestic product, United States dollar exchange rate, inflation and consumption simultaneously and partially towards the imports of processed food and beverages in Indonesia and to find out which independent variable has the dominant influence on imports of processed food and beverages in Indonesia. This study uses secondary data with technical analysis of multiple linear regression. The results of the research simultaneously show that gross domestic product, United States dollar exchange rate, inflation and consumption has a significant effect on imports of processed food and beverages in Indonesia. Partially gross domestic product, inflation and consumption has a positive and significant effect on imports of processed food and beverages in Indonesia while United States dollar exchange rate has a negative and not significant on imports of processed food and beverages in Indonesia. Consumption variable is the dominant influence on imports processed food and beverages in Indonesia.